The Nature of Sensory Experience: the Case of Taste and Tasting - Barry C. Smith (Rosenberg & Sellier, 2016)
Recently, psychologists and neuroscientists have provided a great deal of evidence showing that perceptual experiences are mostly multimodal. As perceivers, we don’t usually recognize them as such. We think of the experiences we are having as either visual, or auditory or tactile, not realising that they often arise from the fusion of different sensory inputs. The experience of tasting something is one such case. What we call ‘taste’ is the result of the multisensory integration of touch taste and smell. These unified flavour experiences provide a challenge when trying to reconcile the underlying processing story with the conscious experience of subjects, but they also challenge assumptions about our access to our own experiences and whether how we conceive of those experiences plays any in role in accounting for their ultimate nature.